Reestructuración de la infraestructura ambiental y recuperación de las cuencas hídricas para la región Sumapaz y Soacha - Plan maestro raíz verde al 2080 - Plan parcial la hoja al 2060 (2019)
As a general proposal, the partial plan is an urban piece included in a territory of 60 hectares between the limits of Soacha and Sibaté more specifically north side of the reservoir of the muña which are distributed in 7 areas of action seeking territorial balance and solving problems more relevant, generating an organic transitional urbanism according to the concepts of new urbanism. Specifically, a series of equipment is proposed distributed in an area of action focused on environmental improvement and in the Sibaté's competitive impulse with the department oriented to social progress and T.O.D. It is the result of the analyzes and diagnoses that were carried out in the area of work under the connection with development plans that are implemented in the Sibaté POT and the concepts of new urbanism. This investigation covers from the history of the territory, the conformation and future projections, the which have had and will have an impact on the site, which generate a footprint important for the benefit in the growth of this, from the moment of the intervention, the proposal will be for the favor of the region and its inhabitants. As conclusive of a result, the architectural project is born having an impact in the departmental, regional and municipal scales. The interaction between the architectural projects, defined from their function, is refers to a cv foundation and environmental social development for the reincorporation society of the province of Soacha and Sumapaz, regional intermodal M.U.R.E and the environmental reforestation and research institute.